Archiving Cultures: Bridging the Gap between Material and Immaterial Heritage (KULT_online, 2025)
In Archiving Cultures, Jeannette Bastian guides the reader through a compelling exploration of what ‘cultural archives’ are. She explores how diverse communities express and document their heritage and collective memories. She also considers the reasons behind intangible forms of expression, as well as their function as archival records. Analyzing several forms of externalizing memories and knowledge beyond written text, she shows their relevance as records for their communities. The next challenge for archivists, cultural policymakers, and everyone concerned with preserving cultural expressions is to determine how they can contribute to this endeavor.